Discourse Analysis on the Cohesion of Descriptive Writing Produced by Students of UIN RIL Lampung. - Puspita Nurul; Umar Al Faruq A Hasyim (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2017)
Discourse analysis considered important for EFL learners. It is because mastering discourse will arise comprehensive communication, especially in written text. One of discourse issues are cohesion. It is beneficial for connecting among ideas of the text. More technically, cohesion appears by applying cohesive devices such as references, ellipsis, substitution, conjunction and lexical cohesion. This research is descriptive one that aims at describing the usage of cohesive devices on the descriptive paragraphs written by 21 students of UIN RIL Lampung. The result found that the students mostly use references as the cohesive devices on their paragraphs. In addition, the references used were pronouns he and she. The pronoun he used by 14 students and the pronoun she used by 7 students. Key words: Discourse analysis, Cohesion, Descriptive writing